Central cellular signaling pathways involved with the regulation of lipid metabolism in the liver: a review - Rute Lopes; Moema Souza Santana; Carla Rios da Cruz; Rafael Bianchini Fulindi; Ana Maria Minarelli Gaspar; Paulo Inácio da Costa (Acta Scientiarum. Biological Sciences, 2020)
The liver is primarily responsible for energy homeostasis and the regulation of lipid, carbohydrate and protein metabolism. Lipid metabolism consists of distributing lipids to peripheral tissues or ensuring their return to the liver to be reprocessed. Additionally, cellular metabolism is regulated by several molecules in different signaling pathways. Lipid homeostasis in the liver is mainly regulated by AKT, AMPK, SREBP, PPAR, and JNK. The PI3K/AKT/mTOR signaling pathway results in the biosynthesis of macromolecules and regulates lipogenesis and the expression of lipogenic genes. AMPK is an energy sensor that regulates metabolism and is activated when stored ATP is depleted, and it is responsible for the suppression of several key lipogenic factors in the liver related to cholesterol and fatty acid synthesis. SREBPs control lipogenic gene expression and cholesterol metabolism and act in the nutritional regulation of fatty acids and triglycerides. The continued activation of SREBPs is associated with cellular stress, inflammation and ultimately steatosis. PPARs are intrinsically important regulators of lipid metabolism. These genes are essential to various metabolic processes, especially lipid and glucose homeostasis, and can play a role in cell differentiation. JNK signaling is related to insulin resistance and its activation results in decreased mitochondrial activity and fat accumulation. Therefore, the study of cell signaling pathways related to lipid metabolism and liver function may help to identify abnormalities and develop strategies to manage and regulate metabolic disorders and resulting complications.